Categorization of patients with pulmonary embolism by Charlson comorbidity index - Keller, Karsten; Schmitt, Volker H.; Hahad, Omar; Espinola-Klein, Christine; Münzel, Thomas; Lurz, Philipp; Konstantinides, Stavros; Hobohm, Lukas (The American journal of medicine, 2024)
Background - Short-term outcomes of pulmonary embolism are closely related to right ventricular dysfunction and patient's hemodynamic status, but also to individual comorbidity profile. However, the impact of patients’ comorbidities on survival during pulmonary embolism might be underrated. Although the Charlson Comorbidity Index (CCI) is the most extensively studied comorbidity index for detecting comorbidity burden, studies analyzing the impact of CCI on pulmonary embolism patients’ survival are limited. - Methods - We used the German nationwide inpatient sample to analyze all hospitalized patients with pulmonary embolism in Germany 2005-2020 and calculated CCI for each patient, compared the CCI classes (very low: CCI = 0 points, mild: CCI = 1-2 points, moderate: CCI = 3-4, high severity: CCI >4 points) and impact of CCI class on outcomes. - Results - Overall, 1,373,145 hospitalizations of patients with acute pulmonary embolism (53.0% females, 55.9% aged ≥70 years) were recorded in Germany between 2005 and 2020; the CCI class stratified them. Among these, 100,156 (7.3%) were categorized as very low; 221,545 (16.1%) as mild; 394,965 (28.8%) as moderate; and 656,479 (47.8%) as patients with a high comorbidity burden according to CCI class. In-hospital case fatality increased depending on the CCI class: 3.6% in very low, 6.5% in mild, 12.1% in moderate, and 22.1% in high CCI class (P < .001). CCI class was associated with increased in-hospital case fatality (odds ratio 2.014; 95% confidence interval, 2.000-2.027; P < .001). - Conclusion - Our study results may help practitioners to better understand and measure the association between an aggravated comorbidity profile and increased in-hospital case fatality in patients with pulmonary embolism.